## (x+1)^2-5=x^2+11 x-5x/6+1/3=2-x/3 x-2/3-2x-3/4=x-1 Giúp mình giải với ạ

Question

(x+1)^2-5=x^2+11
x-5x/6+1/3=2-x/3
x-2/3-2x-3/4=x-1
Giúp mình giải với ạ

in progress 0
1 tháng 2021-08-05T01:35:27+00:00 2 Answers 5 views 0

1. #DyHungg

a) (x+1)²-5=x²+11

⇔x²+2x+1-5=x²+11

⇔x²-x²+2x=-1+5+11

⇔2x=15

⇔x=15/2

Vậy S={15/2}

b) (x-5x)/6+1/3=(2-x)/3

⇔(3(x-5x))/18+6/18=(6(2-x))/18

⇔3x-15x+6=12-6x

⇔3x-15x+6x=12-6

⇔-6x=6

⇔x=-1

Vậy S={-1}

c) (x-2)/3-(2x-3)/4=x-1

⇔(4(x-2))/12-(3(2x-3))/12=(12(x-1))/12

⇔4x-8-6x+9=12x-12

⇔4x-6x-12x=8-9-12

⇔-14x=-13

⇔x=13/14

Vậy S={13/14}

2. Đáp án: + Giải thích các bước giải:

a//

(x+1)^2 – 5 = x^2 + 11

\Leftrightarrow x^2 + 2x = x^2 + 15

\Leftrightarrow x^2 + 2x – x^2 = x^2 + 15 – x^2

\Leftrightarrow 2x = 15

\Leftrightarrow x = 15/2

Vậy S = { 15/2 }

b//

(x-5x)/6 + 1/3 = (2-x)/3

\Leftrightarrow (x-5x)/6 + 2/6 = (2(2-x))/6

\Leftrightarrow (x-5x) + 2 = 2(2-x)

\Leftrightarrow -4x + 2 = -2x + 4

\Leftrightarrow -4x – 2x = 2

\Leftrightarrow -2x = 2

\Leftrightarrow x = -1

Vậy S = { – 1 }

c//

(x-2)/3 – (2x-3)/4 = x – 1

\Leftrightarrow 4(x-2) – 3(2x-3) = 12(x-1)

\Leftrightarrow 4x – 8 – 6x + 9 = 12x – 12

\Leftrightarrow -2x + 1 = 12x – 12

\Leftrightarrow -2x – 12 = 12x – 13 – 12x

\Leftrightarrow -14x = -13

\Leftrightarrow x = 13/14

Vậy S = { 13/14 }`